Penanggulangan Stunting melalui Peningkatan Partisipasi Masyarakat dengan Sosialisasi dan Edukasi Stunting di Desa Sukorejo - Naja, Farda Nihayan; Ramadhani, Nida Fitria; Askaffi, Tegar Maulana (Dharma: Jurnal Pengabdian Masyarakat, 2022)
Stunting or failure to thrive in toddlers is a condition in which toddlers have a length or height that is less than their age due to chronic malnutrition. The danger of stunting has become the main focus of national nutrition problems in Indonesia, this can be seen from Indonesia's SDG indicator which states the stunting reduction target of 40%. Sukorejo is a village located in Mojotengah District, Wonosobo Regency, Central Java which has stunting cases of around 15 toddlers. The low level of education and the presence of early marriage contribute to the impact of stunting in Sukorejo. In solving concerns regarding stunting in Sukorejo, the solution that can be applied is through increasing community participation through socialization and education on stunting as stunting prevention in Sukorejo. The target of this activity is 10 pregnant women in Sukorejo. The implementation of service activities in the form of stunting socialization and education to increase community participation in Sukorejo is considered effective and able to help overcome stunting in Sukorejo.